All-site alloyed perovskite for efficient and bright blue light-emitting diodes - Yu Chen; Ruishan Wang; Gunnar Kusch; Bo Xu; Chenjie Hao; Chen Xue; Lu Cheng; Lin Zhu; Jingmin Wang; Hai Li; Rachel A. Oliver; Nana Wang; et al. (Nature Communications)
Abstract Perovskite light-emitting diodes have drawn great attention in the fields of displays and lighting, especially for applications requiring high efficiency and high brightness. While three-dimensional perovskite light-emitting diodes hold promise for achieving higher brightness compared to low-dimensional counterparts, efficient blue three-dimensional perovskite light-emitting diodes have remained a challenge due to defect formation during the disordered crystallization of multiple A-cation perovskite. Here we demonstrate an all-site alloy method that enables sequential A-site doping growth of formamidinium and cesium hybrid perovskite. This approach significantly reduces the trap density of the perovskite film by approximately one order of magnitude. Consequently, we achieve efficient and bright blue perovskite light-emitting diode with an external quantum efficiency of 23.3%, a luminous efficacy of 33.4 lm W−1, and a luminance of approximately 5700 cd m−2 for the emission with a peak at 487 nm. This work provides a strategy for growing high-quality multicomponent perovskite for optoelectronics.